Fabrication and optimization of the stereolithographic 3D printing of particle composites using titanium fillers & photocurable resins - Low, Ker Yang (Nanyang Technological University, 2021)
Stereolithography (SLA) is a form of 3D printing technology that prints models in a layer-by-layer fashion, using photochemical processes where ultraviolet light causes the crosslinking of the molecules in the photocurable liquid resin. Recently, much interest has been shown in the field of SLA 3D printing of composite materials, due to the possibility of improved mechanical properties compared to its pure polymeric counterparts, as well as acting as a potential low-cost method to print metallic structures. This study investigates the effects of ultraviolet (UV)/thermal curing as well as adding titanium fillers on the mechanical properties and print success rates of 3D printed resin samples. The optimal curing conditions for the pure resins used in this study were determined, and it was discovered that the addition of metal fillers do not necessarily enhance the mechanical properties of the resin samples. Finally, this study investigates reasons behind the issues as to why composite materials of sufficiently high metal concentrations are unable to be printed yet, and explores various solutions to overcome these problems, some of which ultimately achieve a degree of success.